Pemutihan Status Pekerja Prekariat (Studi Pekerja Kontrak dan Outsourcing di Kawasan Industri Makassar) - Nur Adhi, Rakhmat; Utomo, Jepri (Paraduta : Jurnal Ekonomi dan Ilmu-Ilmu Sosial, 2025)
This study aims to examine the process of employment status normalization among precarious workers in the Makassar Industrial Zone. The research focuses specifically on workers employed under contract and outsourcing agreements. A qualitative approach was employed, with in-depth interviews as the primary method of data collection. Additionally, observations were conducted to gain a clearer picture of the working conditions experienced by the informants. Secondary data from various documents were also gathered to enrich the understanding of worker vulnerability and the status normalization process. Informants were selected using purposive sampling, involving five individuals: four workers and one representative from an outsourcing agency management. The findings reveal two common patterns in the normalization process. First, permanent workers are reassigned as contract workers under the justification of corporate efficiency and crisis. Second, contract workers are reclassified as outsourced workers. Rather than being a result of internal company issues, status normalization reflects the precarious workers’ inability to secure their employment status and protect their labor rights. Keywords: Employment Status Normalization, Precarious Workers, Labor Market Flexibility.